Effect of match location on the playing style of teams coached by `Pep` Guardiola - Pueyo, L.; Murillo, V.; Álvarez, J.; Sarmiento, A.; Amatria, M. (Frontiers in Psychology, 2024)
Introduction: Analysis in football seeks to find the performance factors that bring teams closer to success.